2020
DOI: 10.1080/19476337.2020.1794980
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical study of nixtamalized corn masa and tortillas fortified with “chapulin” (grasshopper, Sphenarium purpurascens) flour

Abstract: The objective of this work was to study the physicochemical properties of nixtamalized corn flour (NCF) enriched with grasshopper Sphenarium purpuracens, "chapulin" flour (ChF) at 2, 6, and 10% w/ w. Bromatological, vibrational, mineral, structural, thermal, viscosity, textural, and acceptability analyses were done. It was found that the ChF is rich in alkali-soluble proteins and the inductively coupled plasma mass spectrometry (ICP) analysis showed the presence of important minerals to human health like K (42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 24 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…When compared to the Ca content of white and blue maize handmade tortillas (155 and 136 mg/100 g, respectively) [ 37 ], only the RT0 presented a slightly lower value. The addition of Sphenarium purpuracens [ 18 ] and nopal powder [ 11 ] also led to an increase in the mineral content. According to the Dietary Guidelines for Americans [ 35 ], the Recommended Dietary Allowance (RDA) of Ca, P, and Mg for men and women from 14 years old and more is 1000–1300 mg, 700–1250 mg, and 360–420 mg, respectively, while the Adequate Intake (AI) of K is 2300–3400 and the Chronic Disease Risk Reduction Level (CDRR) of Na is a maximum of 2300 mg. One hundred grams (roughly three tortillas ) of BT9 would cover between 47 and 60% of the Ca RDA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When compared to the Ca content of white and blue maize handmade tortillas (155 and 136 mg/100 g, respectively) [ 37 ], only the RT0 presented a slightly lower value. The addition of Sphenarium purpuracens [ 18 ] and nopal powder [ 11 ] also led to an increase in the mineral content. According to the Dietary Guidelines for Americans [ 35 ], the Recommended Dietary Allowance (RDA) of Ca, P, and Mg for men and women from 14 years old and more is 1000–1300 mg, 700–1250 mg, and 360–420 mg, respectively, while the Adequate Intake (AI) of K is 2300–3400 and the Chronic Disease Risk Reduction Level (CDRR) of Na is a maximum of 2300 mg. One hundred grams (roughly three tortillas ) of BT9 would cover between 47 and 60% of the Ca RDA.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the results found in this study, Argüello-García et al [ 28 ] found that increasing the content of J. curcas L. flour led to a decrease in hardness, which was attributed to a higher protein content. Masas prepared with corn flour and J. curcas L. flour presented lower values of hardness (2.30–3.13 N [ 28 ], similar to nixtamalized corn masa with Sphenarium purpurascens flour (0.59–0.81 N) [ 18 ]. Nixtamalized maize masas obtained using several nixtamalization processes presented similar values (4–15 N) [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, FAO recommended that people can supplement their daily diet with edible insects, since they are consumed in some stage of their life cycle as food resources (van Huis et al, 2013). Currently, over one thousand identified species have historically been recorded and consumed by one third of the world's population, mostly in Asia, Latin America, and Africa, for more than two thousand years (Jiménez et al, 2020;Raheem et al, 2018). Asian people started cultivating silkworms (Bombyx mori) artificially 5200 years ago (Ghosh et al, 2017;Yi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%